METHODOLOGY COMPRESSION OF VIDEOINFORMATION IN THE CRYPTOGRAPHIC SYSTEMS - Barannik, V.; Sidchenko, S.; Larin, V. (Science-based technologies, 2011)
Substantiation of is spent that for increase of efficiency of processing and delivery of the video data with using information communication systems of real time is required to carry out cryptographic enciphering simultaneously with the organization of compact representation.